FORMAÇÃO DE PROFESSORES INDÍGENAS EM MATO GROSSO DO SUL: UM ESTUDO SOBRE AS LUTAS, CULTURAS E IDENTIDADES. - Vlademir Sergio Bondarczuk (2024)
This doctoral thesis investigates the training of indigenous teachers in the state of Mato Grosso do Sul, Brazil. The objective is to analyze the impact of indigenous teacher training courses in Mato Grosso do Sul on the struggles for the valorization of the culture, knowledge, identities, and Amerindian thought of the Terena, Kinikinau, Kadiwéu, Guarani-Nhandeva, and Guarani-Kaiowá peoples, as presented in the interviews. The research utilizes the methodology of Oral History and is based on the Perspectivism and Multinaturalism theory of Viveiros de Castro. Additionally, it is connected to the History of Mathematics Education Research Group (Hemep), which aims to map the training of teachers who teach and have taught mathematics in Mato Grosso do Sul. The research expands the national mapping that has been carried out by the Oral History and Mathematics Education Group (Ghoem) on teacher training and documents the experiences of interviewees belonging to the Terena, Kinikinau, Kadiwéu, Guarani-Nhandeva, and Guarani-Kaiowá peoples, contributing to the strengthening of intercultural education and the recognition of the specific demands of these peoples. The research is qualitative and based on semi-structured interviews with indigenous teachers who have graduated from the following training courses: Indigenous Teaching by the Catholic Education Association of Mato Grosso do Sul (AEC), Kadiwéu/Kinikinau Teaching, Ará Verá Teaching, Indigenous Teaching “Povos do Pantanal,” Indigenous Higher Education, Teko Arandu Indigenous Intercultural Teaching, and Indigenous Intercultural Teaching “Povos do Pantanal,” as well as documents found. The narratives reveal challenges related to the devaluation of traditional knowledge, deficiencies in educational structures, and conflicts with the dominant education system. The training courses emerge as catalysts for the valorization of indigenous culture and knowledge, empowering teachers to claim an intercultural educational space. However, the graduates emphasize the possibilities of redefining the school curriculum, revitalizing native languages, and strengthening indigenous identities within communities. The fundamental role of the training courses is demonstrated both at the individual level, positively impacting the lives of the graduates, and at the collective level, by contributing to cultural revitalization and the struggle for territorial and educational rights.